CISSP Practice Questions Exam Cram, Third Edition - Gregg, Michael (Pearson IT Certification, 2012)
The Publisher regrets that the CD/DVD content for this title cannot be made available Online. CISSP Practice Questions Exam Cram, Third Edition complements any CISSP study plan with 1,001 practice test questions in the book - all supported by complete explanations of every answer. This package's highly realistic questions cover every area of knowledge for the new CISSP exam. Covers the critical information you'll need to know to score higher on your CISSP exam! Features 1,001 questions, organized to reflect the current CISSP exam objectives so you can easily assess your knowledge of every topic. Each question includes a detailed answer explanation. Provides complete coverage of the Common Body of Knowledge (CBK). Use our innovative Quick Check Answer Key to quickly find answers as you work your way through the questions.
Keywords: Information technology -- Security measures; Computer security -- Management; Computer networks -- Security measures; Data protection; Technologie de l'information; Sécurité; Mesures; Sécurité informatique; Gestion; Réseaux d'ordinateurs; Sécurité; Mesures; Protection de l'information (Informatique); Computer networks; Security measures; Computer security; Management; Information technology; Security measures